2017
DOI: 10.1155/2017/9195163
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Recurrence and Malignant Transformation of Sinonasal Inverted Papilloma

Abstract: Sinonasal inverted papilloma is a relatively rare disease; however, it is prevalent enough for every ENT practitioner to encounter it several times throughout medical routines. Despite the developments in experimental and clinical medicine as well as surgical techniques, our knowledge of this disease is still inadequate. With improved imaging and better diagnostic techniques, proper diagnosis and qualification for surgical approaches leave no doubt. Although the endoscopic approach seems to be the gold standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 51 publications
0
23
0
9
Order By: Relevance
“…The aetiology of ISPs and OSPs is not fully understood, although several studies have suggested that HPV infection, bacterial infections and tobacco smoking may be risk factors . Moreover, a recent case–control study found a significantly increased risk among subjects previously exposed to organic solvents, welding fumes and nickel compounds, extending previous observations indicating an unusually high proportion of cases in those employed in the steel industry and in manufacturing .…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…The aetiology of ISPs and OSPs is not fully understood, although several studies have suggested that HPV infection, bacterial infections and tobacco smoking may be risk factors . Moreover, a recent case–control study found a significantly increased risk among subjects previously exposed to organic solvents, welding fumes and nickel compounds, extending previous observations indicating an unusually high proportion of cases in those employed in the steel industry and in manufacturing .…”
Section: Introductionmentioning
confidence: 58%
“…While ESPs are only rarely associated with sinonasal squamous cell carcinomas (SCCs), ISPs and OSPs show malignant transformations in 2%–27% of cases and can be associated with synchronous or metachronous SCCs (ISP‐SCC) . Moreover, sinonasal SCCs may also arise as primary malignant tumours without clinical or pathological evidence of an associated papilloma ( de novo SCC), and are characterised by a poor prognosis with a high tendency to recur and metastasize to various distant sites . Surgical resection is the treatment of choice for such neoplasms and, in selected cases of malignancies, adjuvant treatments can be associated to improve survival rates and reduce the risk of recurrences …”
Section: Introductionmentioning
confidence: 99%
“…The specific mechanisms of its development remain unclear. The common symptoms associated with the condition include unilateral nasal obstruction, epistaxis, and cheek pain, which are not specific . Endoscopy, computed tomography, and magnetic resonance imaging are usually not able to determine whether the SCC arose from the malignant transformation of existing IPs .…”
Section: Discussionmentioning
confidence: 99%
“…Inverted papilloma is a challenging pathology because of its tendency to recurrence, invasive nature and possibility of malignancy. Etiology is still unclear, though there have been mentioned some risk factors, with no causality proven, such as chronic inflammation, smoking and viral infections 5 . Despite the advances made in detection of the viral genome in the last decades, viral implication in IP has not been demonstrated and fully accepted yet.…”
Section: Discussionmentioning
confidence: 99%
“…Krouse classification directs the surgical approach 7 . Starting from this classification, stage T1 and T2 inverted papilloma can be treated endoscopically, while stage T3 and T4 might require a combined or external approach 5 . Besides the Krouse classification, another important factor in choosing a surgical approach is identifying the point of origin.…”
Section: Discussionmentioning
confidence: 99%